Cistrons encoding Escherichia coli heat-labile toxin. - Dallas, W S (1979)
The structure and products of the two cistrons encoding the Escherichia coli heat-labile toxin (LT) were studied. The LT deoxyribonucleic acid (DNA) region had been isolated as part of a DNA fragment from the plasmid P307, and this fragment was joined to the cloning vector pBR313. Deletion mutations of various lengths were introduced into the LT DNA region and into the adjacent DNA sequences. Analysis of the deletions indicated that the maximum size of the LT DNA region was 1.2 x 10(6) daltons. Two proteins of 11,500 daltons and 25,500 daltons had been shown to be encoded by the LT DNA region. The functions of these LT gene products were investigated. The 11,500-dalton protein had an adsorption activity for Y-1 adrenal cells, and this protein was shown to form aggregates of four or five monomers. The 25,500-dalton protein was shown to have an adenylate cyclase-activating activity. The two cistrons encoding for each of the LT proteins have been located on a genetic map of the LT DNA region. Both cistrons are probably transcribed from the same promoter.